Effects of moderate shade and irrigation with eutrophicated water on the nitrogen economy of Mediterranean oak seedlings - Castro-Díez, Pilar; Navarro, Javier; Maestro, Melchor (Flora - Morphology, Distribution, Functional Ecology of Plants, 2008)
We evaluated the effects of moderate shade (43% vs. 100% of full sunlight) and irrigation with eutrophicated river water (daily vs. alternate-day watering) on growth and nitrogen economy of seedlings of three Mediterranean oak species, two evergreen (Quercus coccifera, Quercus ilex subsp. ballota) and a deciduous (Quercus faginea), grown in pots outdoors. Seedling biomass, N pool, N concentration and N losses by litter fall were measured at the beginning (March 2002) and end (November 2002) of a growing season. All species showed an increase of biomass and N pool under shade and/or high irrigation, while only Q. coccifera – from more arid regions – did the same under full sunlight and low irrigation. At the end of the experiment, biomass of the evergreens was higher in shade than in sun, and in high than in low irrigation, while Q. faginea – from more humid zones – responded to irrigation only. Shade-induced growth was accompanied by a decline in N concentration in the evergreens, but irrigation reduced N concentration only of Q. faginea. Shade, but not irrigation, reduced above-ground N loss. We conclude that both treatments differentially affected the evergreen and the deciduous oaks, probably due to differences in plant hydraulic and stomatal conductance. Although both treatments have similar effects on the growth of evergreens, they produced different effects on seedling N economy, which may have important consequences on future ﬁeld seedling performance
Keywords: deciduous tree; Drought stress; evergreen tree; leaf shedding; Quercus; seedling growth